2007
DOI: 10.1080/15326900701326584
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Prior Experience in Language Acquisition

Abstract: Learners exposed to an artificial language recognize its abstract structural regularities when instantiated in a novel vocabulary (e.g., Gómez, Gerken, & Schvaneveldt, 2000; Tunney & Altmann, 2001). We asked whether such sensitivity accelerates subsequent learning, and enables acquisition of more complex structure. In Experiment 1, pre‐exposure to a category‐induction language of the form aX bY sped subsequent learning when the language is instantiated in a different vocabulary. In Experiment 2, while naíve le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 42 publications
1
44
0
Order By: Relevance
“…Also, participants were required to learn simpler contingencies before learning more complex contingencies. Learning the simpler contingencies could have bootstrapped learning the more complex contingencies (e.g., see Lany & Gomez, 2008;Lany, Gomez, & Gerken, 2007). Participants in the present study, unlike those in the Millward and Reber study, locations from left to right, respectively, Table 2 presents some of the 96 contexts and the probabilities with which successors followed contexts.…”
Section: Methodsmentioning
confidence: 99%
“…Also, participants were required to learn simpler contingencies before learning more complex contingencies. Learning the simpler contingencies could have bootstrapped learning the more complex contingencies (e.g., see Lany & Gomez, 2008;Lany, Gomez, & Gerken, 2007). Participants in the present study, unlike those in the Millward and Reber study, locations from left to right, respectively, Table 2 presents some of the 96 contexts and the probabilities with which successors followed contexts.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to Lany et al (2007;Experiment 3), the non-adjacent dependency pairs were divided into two subsets, each sharing the same set of six intervening items in the second position (aX 1-6 b and cX 1-6 d vs. eY 1-6 f and gY [1][2][3][4][5][6] h; adjacent transitional probability = .17, see Figure 1). Therefore, for a given participant, two non-adjacent dependency pairs (e.g., jom-mig and zol-vun) were only combined with one secondelement subset (e.g., namie, sluro, hagix, worat, ruxot, and kapek), whereas the other two non-adjacent dependency pairs (e.g., taf-bur and pes-lin) were only combined with the remaining subset of second elements (e.g., hufel, fenar, dosef, witus, dazan, and gunis).…”
Section: Methodsmentioning
confidence: 99%
“…Note that not all observed effects of adjacent on non-adjacent dependency learning are negative. Later studies (Lany & Gómez, 2008;Lany, Gómez, & Gerken, 2007) have shown that if the nonadjacent dependency to be learned has been encountered earlier as an adjacent pair, then non-adjacent dependency learning is facilitated (see also, e.g., Creel, Newport, & Aslin, 2004 for other facilitating factors). In either case, existing evidence suggests a heavy influence of adjacent on non-adjacent dependency learning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have been conducted on humans on the role of previous experiences. For instance, Lany, G´omez and Gerken [22] carried out a study on the role of prior experience in language acquisition. They realized that learner"s prior experiences facilitate the new language learning.…”
Section: Introductionmentioning
confidence: 99%